(untitled) (Research, Society and Development, 2020)
This study aimed to identify sociodemographic characteristics of university students in the last year in the health field, to verify whether they have Common Mental Disorders (CMD) and to investigate the relationship between CMD and the perception of stress and self esteem in this population. This is a quantitative, descriptive and exploratory study, involving students from biomedicine, nursing, nutrition, physical education, pharmacy, physiotherapy and psychology courses, with a sample of 184 university students. The Sociodemographic questionnaire, the Self-Reporting Questionnaire (SRQ-20), the Perceived Stress Scale PSS-14 and the Rosenberg Self Esteem Scale (EAR) were used for data collection. The analysis was performed using the software Statistical Package for the Social Sciences SPSS® version 21, with the adoption of a significance level of 5% (alpha = 0.05) in all analysis. As a result, CMD were present in 116 (63.0%) students. There was a statistically significant association between CMD and stress and between CMD and self esteem (p <0.001), which expresses an extremely significant result. In fact, the expressive prevalence of CMD, associated with the levels of stress and self esteem identified in this study, reveal the immediate need for the insertion of actions and projects by the university, aimed at the well-being of the university population and health promotion mental, considering the scenario prone to illness and the vulnerability of students.